Pengaruh Media Canva Interaktif Terhadap Kemampuan Berhitung Anak Usia 5-6 Tahun Di TK 1-61 Padang - Agnesi Yulika, Thasya; Yulika, Thasya Agnes; Zulminiati; Rakimahwati; Sari, Resti Elma (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
Teachers must be more inventive in developing creative, original, engaging, and enjoyable learning activities to enhance children's comprehension of learning because youngsters lack numeracy skills such as matching, comparing, sequencing, and counting a collection of objects. The purpose of this study is to ascertain how interactive Canva media affects the numeracy abilities of kids in the 5–6 age range at Kartika Kindergarten 1-61 Padang. This study employs a quasi-experimental methodology with a quantitative approach. Techniques for gathering data include documentation and testing. The 50 youngsters who attended Kartika Kindergarten 1-61 Padang made up the study's population. 40 youngsters made up the study's sample, 20 of whom were in the experimental class (class B2) and 20 of whom were in the control class (class B1). The normality, homogeneity, and hypothesis tests were employed in this study's data processing methodology. Using SPSS 30 and the t-test statistical method, hypothesis testing revealed a significance level of less than 0.05. According to the study's findings, the average pre-test and post-test scores for the experimental class that used Canva medium were 13.50 and 18.30, respectively. The mean pre-test and post-test scores in the PowerPoint-using control group were 13.15 and 14.10, respectively. The resulting data were homogeneous and regularly distributed. Furthermore, Ho was rejected and Ha was accepted after the t-test findings showed that the sig value (2-tailed) was <0.001 <0.05. We may conclude that the numeracy skills of the pupils at Kartika Kindergarten 1-61 Padang are significantly impacted by interactive Canva media.